Mesoproterozoic post-orogenic magmatism on the southwestern North China Craton: onset of Columbia breakup - Cui, Junping; Guo, Wei; Ren, Junfeng; Ren, Zhanli; Song, Haoyu; Liu, Guoqing (Frontiers in Earth Science, 2025)
IntroductionThe North China Craton experienced multiple episodes of Mesoproterozoic anorogenic magmatism, which provides critical insights into the breakup process of the Columbia supercontinent. While numerous previous studies have focused on the southern and eastern margins of the craton, the southwestern margin remains relatively understudied, and its tectonic setting is still poorly constrained.MethodsTo investigate the tectonic context of Mesoproterozoic magmatic events along the southwestern margin and their relationship with the breakup of Columbia, this study presents a systematic analysis of the petrology, zircon U–Pb geochronology, and geochemistry of the granite porphyry in the Qi’angou area of Longxian, southwestern North China Craton.ResultsThese data are integrated with geochemical characteristics of other Mesoproterozoic igneous rocks from the western margin to comprehensively analyze the magmatic activity in this region. Zircon U–Pb dating yielded an emplacement age of 1794 ± 10 Ma for the Qi’angou granite porphyry, indicating its formation during the Mesoproterozoic. Geochemical data show that the granite porphyry is peraluminous and belongs to the A2-type granite suite. It is enriched in large-ion lithophile elements (LILE) and depleted in high-field-strength elements (HFSE), with high Rb/Sr ratios (2.95–3.55), pronounced negative Eu anomalies, and low Mg# values, suggesting a crustal derivation.DiscussionCombined with previous studies on coeval intermediate-mafic rocks (1740–1804 Ma)—including calc-alkaline basaltic andesites and high-K calc-alkaline diabases—these findings indicate that the North China Craton underwent extension during the late Paleoproterozoic to early Mesoproterozoic. Upwelling of a mantle plume beneath the southwestern margin triggered lithospheric thinning and partial melting of the upper crust, leading to a series of magmatic events. Comprehensive geochemical features and regional tectonic analysis suggest that the western margin igneous assemblage formed in a post-orogenic intracontinental extensional setting. This represents the initial geological record of the global breakup of the Columbia supercontinent within the North China Craton and provides key chronological constraints for understanding the geodynamic mechanisms of supercontinental fragmentation.